ANALISIS KAUSALITAS KETIMPANGAN PENDAPATAN, KORUPSI DAN KEMISKINAN DI NEGARA LOWER MIDDLE INCOME ASEAN - Hartisa, Novilia; Putri, Dewi Zaini (Jurnal Kajian Ekonomi dan Pembangunan, 2020)
Abstract : This study is to see whether there is a causal relationship betweenincome inequality, corruption and poverty in ASEAN countries. This study uses apanel of data in five lower middle income countries in ASEAN from 2010-2018,using the Vector Auto Regression (PVAR) processing method. From the results ofthe investigation that: (1) There is a causality relationship between incomeinequality and corruption in the five lower middle income countries in ASEAN, (2)There is no causality relationship between income inequality and poverty in thefive lower middle income countries in ASEAN, but only there is a one-wayrelationship of income and corruption in five lower middle income countries inASEAN, (3) There is no causal relationship between corruption and poverty eitherone way or reciprocally in five lower middle income countries in ASEAN.Keyword: Income inequality, corruption and poverty.